HUBUNGAN ANTARA KEBIASAAN MAKAN MEROKOK DAN OLAH RAGA DENGAN KEJADIAN STROKE ISKEMIK BERULANG - Pukovisa Prawiroharjo*, Wiji Lestari**, Salim Harris*** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION LIFESTYLES SUCH AS CONSUMING BEHAVIOR SMOKING AND SPORT HAVE BEEN INVESTIGATED TO HAVE RELATIONSHIPS WITH ISCHEMIC STROKE EVENTS CONSUMPTIONS OF FISH VEGETABLEANDFRUIT AND AEROBIC SPORT ARE PROTECTIVE IN PRIMARY PREVENTION OF ISCHEMIC STROKE CONVERSELY EXCESSIVE COFFEE CONSUMPTION AND SMOKING ARE RISK FACTORS OF ISCHEMIC STROKE EVENT BUT THERE WERE NO AVAILABLE STUDY WHICH INVESTIGATES THOSE FACTORS AND THEIR RELATIONSHIP WITH RECURRENT ISCHEMIC STROKE EVENTS RISE IN PURPOSE OF SECONDARY PREVENTIVE EFFORTS